Al-Fatonah Mosque Information System Web-based - Nurul Aghnia; Surya Ade Saputera; Sri Handayani; Yetman Erwadi (Penerbit Jurnal Indonesia, 2023)
Al-Fatonah Mosque is a mosque located on Jalan Waiting, Bengkulu, which is a relatively new mosque. The Al-Fatonah Mosque is still largely unknown to the general public about its existence and activities. The aim of this research is to enliven or increase the congregation at the Al-Fatonah Mosque in positive activities, with the aim of research in the web-based information system of the Al-Fatonah Mosque using the RAD (Rapid Application Development) method. This research uses the rapid application development method, because this method is faster to develop so it does not require a long time to create the Al-Fatonah mosque system. The problem formulation in this research is how to create an information system for introducing the Al-Fatonah mosque to increase the congregation at the Al-Fatonah mosque using the RAD (Rapid Application Development) method. It is hoped that the results of this research will have a positive impact on local residents, outsiders and the mosque management by providing more information to residents about the activities and existence of the mosque.